AN ANALYSIS OF TEACHER TALK IN ENGLISH FOREIGN LANGUAGE CLASSROOM - Sri Ananda Pertiwi (PT Akselerasi Karya Mandiri, 2023)
The present study investigates errors teachers produce while teaching in an English Foreign Language (EFL) classroom. The respondent involved in this study is an English teacher at a favourite junior high school in Makassar, South Sulawesi. This research is conducted through descriptive qualitative design. The instrument used is recording. The data analysis shows that the teacher makes phonological and syntactical errors in using English as the language of instruction in teaching. The most frequent errors made by the teacher in phonology is on pure vowel and diphthong, either syntax on the incomplete form of questions and word order.